How Does Science Come to Speak in the Courts? Citations Intertexts, Expert Witnesses, Consequential Facts, and Reasoning - Bazerman, Charles (2009)
Citations, in their highly conventionalized forms, visibly indicate each texts explicit use of the prior literature that embodies the knowledge and contentions of its field. This relation to prior texts has been called intertextuality in literary and literacy studies. Here, Bazerman discusses the citation practices and intertextuality in science and the law in theoretical and historical perspective, and considers the intersection of science and law by identifying the judicial rules that limit and shape the role of scientific literature in court proceedings. He emphasizes that from the historical and theoretical analysis, it is clear that, in the US, judicial reasoning is an intertextually tight and self-referring system that pays only limited attention to documents outside the laws, precedents, and judicial rules. The window for scientific literature to enter the courts is narrow, focused, and highly filtered. It serves as a warrant for the expert witnesses' expertise, which in turn makes opinion admissible in a way not available to ordinary witnesses